Relationship Between Nb-Ta Enrichments and Highly-Fractionated Granitic Magma Evolution in South China: Geochronological, Zircon Hf Isotopic and Geochemical Evidence From Jianfengling Granite - Ze-Yi, Chen; Yong-Jun, Shao; Han-Tao, Wei; Cheng, Wang (Frontiers in Earth Science, 2022)
The Jianfengling granite is an important ore-forming rock unit in the Xianghualing orefield in Nanling region (South China), and its magmatic evolution is vital to understand the regional niobium (Nb)-tantalum (Ta) mineralization. The Jianfengling granite comprises three gradual transitional lithofacies: porphyritic biotite monzogranite (mesophase facies), biotite monzogranite (transition facies) and topaz biotite monzogranite (central facies). All the three biotite monzogranite lithofacies are characterized by being rich in SiO2 and Al2O3, poor in TFe2O3, CaO, MgO, TiO2, MnO and P2O5, and are peraluminous high-K calc-alkaline. These rocks are remarkably enriched in Rb, Th, U, Nb and Ta, strongly depleted in Ba and Sr, and slightly depleted in Zr. The LREE/HREE decreases gradually from porphyritic biotite monzogranite, through biotite monzogranite to topaz biotite monzogranite, with increasing convex (“M-type”) lanthanide tetrad effect, which similar to the highly-fractionated granite. The high Th-U (Thavg. = 2051.56°ppm; Uavg. = 1,498.23°ppm, respectively) and low Th-U (Thavg. = 708.14°ppm; Uavg. = 441.57°ppm, respectively) zircon grains from porphyritic biotite monzogranite yielded weighted average 206Pb/238U ages of 161.3 ± 1.6 Ma (MSWD = 1.3, n = 13) and 158.7 ± 2.0 Ma (MSWD = 1.7, n = 13), respectively, consistent with the large-scale magmatic-mineralization event in the Nanling region (ca. 160–150 Ma). The εHf(t) values of the high Th-U (-6.48 to -2.51) and low Th-U (-6.58 to -1.12) zircon grains from the porphyritic biotite monzogranite indicate that the causative magma was formed from partial melting of the Mesoproterozoic Cathaysian basement rocks in a lithospheric extension setting. The Nb and Ta contents increase with fluorine from the porphyritic to topaz biotite monzogranite, indicating that the Nb-Ta enrichment may have caused by the gradual increase of fluxing content (fluorine) during the fractionation of the Jianfengling granitic magma.